Analisis aspek pemasaran dalam kelayakan bisnis pada pegadaian syariah Kauman Kota Malang - Salsabila, Gardena; solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the marketing strategy of Pegadaian Syariah Kauman Malang City with a qualitative approach. Data were obtained through interviews and direct observation at the research location. The results show that the marketing strategy includes four main aspects: (1) Product, offering sharia services such as Arrum Haji and Amanah with attractive naming and payment flexibility; (2) Price, set fairly and competitively according to sharia contracts; (3) Place, utilizing a strategic location in the center of Malang City, supported by digital services; and (4) Promotion, through social media, WhatsApp, pamphlets, as well as discounted fees and ease of digital payment. This strategy supports ease of access, sharia compliance, and customer satisfaction.